Water Level Detection System based on Arduino and LabVIEW for Flood Monitors using Virtual Instrumentation - Sabar Sabar; Dewi Maulidah Nur Anjani; Sastra Kusuma Wijaya (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
This virtual instrumentation system based on Arduino and LabVIEW aims to detect the water level using a water level sensor. The water level sensor used to measure the water level is the Funduino type. This sensor and the buzzer module are connected to the Arduino Uno to transmit data to LabVIEW. When the water has reached a certain height, this sensor will detect the water level. When the water has reached the set point, this sensor will sound a buzzer as a sign that the water is full. Based on the experimental results, it is found that the tension value affects the volume of the experiment site. Where the greater the volume used will produce a large voltage, and vice versa. Furthermore, the graph results obtained that are still away from the linearity of a regression function with a value of y = 0.0079x + 1.8561 and R² = 0.4298.